Branding UMKM Usus-usus Reog Ponorogo melalui Pembuatan Media Sosial Instagram Kolorin.id untuk Meningkatkan Penjualan - Buntoro, Ghulam Asrofi; Annas, Rafi Nur; Ningrum, Dewi Puspita; Septyana, Dinda; Setiawan, Didik; Hanafi, Afip Choirul; Saputro, Arfindo Adimas Eko; Yahya, Muhammad Fachrul (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2023)
This community service aims to increase the marketing of MSMEs "Usus Usus Reog" through branding campaigns using the Instagram platform and brand awareness. The methods used include initial surveys, community education, training, product logo creation, and digital marketing support. The results showed a significant increase in MSME Instagram account followers, the use of brand-related hashtags, and higher follower engagement. Although the direct impact on sales cannot be accurately measured, the benefits of this approach in strengthening brand recognition and building better relationships with customers can be seen. A comprehensive approach that includes education and training, in addition to brand promotion, has a significant positive impact. Therefore, we recommend continuing and expanding education and training efforts for MSME owners so that they become more proficient in utilizing the potential of Instagram and other media platforms.